2018
DOI: 10.1093/icesjms/fsy066
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic cameras reveal high levels of crepuscular and nocturnal shore-based recreational fishing effort in an Australian estuary

Abstract: Although recreational fishing at night is a popular activity, crepuscular and nocturnal fishing effort and catches are often unaccounted for in fisheries assessments. Here, we present a method for estimating 24-h shore-based recreational fishing effort involving the analysis of data from dual-lens thermographic cameras. Cameras were installed at three sites along the foreshore in Peel-Harvey Estuary, a Ramsar Wetland in Western Australia. Stratified random sampling was used to select days for image analysis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…For example, Greenberg and Godin (2015) developed Timelapse, a computer application that efficiently combines photo viewing and data extraction. In other studies, photos captured at automated intervals were condensed into video format, allowing for quick progression through periods of inactivity or nontarget boat‐ramp use during photo analysis (Blight and Smallwood 2015; Stahr and Knudsen 2018; Taylor et al 2018). We analyzed photos for every day on which our cameras were operational, but extensive photo logs could be subsampled and daily mean values of fishing effort extrapolated to unsampled days to reduce personnel time and project costs (Keller et al 2016; Powers and Anson 2016; Stahr and Knudsen 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Greenberg and Godin (2015) developed Timelapse, a computer application that efficiently combines photo viewing and data extraction. In other studies, photos captured at automated intervals were condensed into video format, allowing for quick progression through periods of inactivity or nontarget boat‐ramp use during photo analysis (Blight and Smallwood 2015; Stahr and Knudsen 2018; Taylor et al 2018). We analyzed photos for every day on which our cameras were operational, but extensive photo logs could be subsampled and daily mean values of fishing effort extrapolated to unsampled days to reduce personnel time and project costs (Keller et al 2016; Powers and Anson 2016; Stahr and Knudsen 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate the proportion of fishing trips that occurred at night, but some trips did begin and end at night. Using thermographic cameras that could photograph fishers in the dark, Taylor et al (2018) demonstrated the importance of including crepuscular and nighttime fishing in total fishing effort estimates. Stahr and Knudsen (2018) suggested that missing nighttime fishing via their boat ramp cameras, which did not operate after dark, was likely responsible for differences in fishing effort estimates between a boat ramp camera and an in‐person, access‐point creel survey that did continue into nighttime.…”
Section: Discussionmentioning
confidence: 99%
“…If the study locations were smaller, that is focusing on counting fishers on the training walls and river bar area; then, there would be additional safety and cost benefits in using drone‐based surveys. Data that contribute to the effective management of natural resources are increasingly being collected via remote sensing technologies (Beckmann et al., 2019; Steffe et al., 2017), with expanding contributions from novel techniques, such as smartphone applications (Venturelli, Hyder, & Skov, 2017) and innovative camera‐based methods (Flynn et al., 2018; Hartill, Payne, Rush, & Bian, 2016; van Poorten & Brydle, 2018; Taylor et al., 2018). Additionally, citizen science may be appropriate for efficient data collection (Fairclough, Brown, Carlish, Crisafulli, & Keay, 2014; Fulton et al., 2019) and foster a culture of voluntary catch reporting.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 85 semi-structured interviews were conducted between November 2018 and November 2019, during daylight hours to collect network data, respondents' attitudes and perceptions toward information sharing efficiency, and individuals' demographics. Note that more recently, monitoring by DPIRD has found a significant number of recreational fishers fishing throughout the evening (Taylor et al, 2018). No interviews were carried out at during the night and therefore we have no information on whether the night fishers represent a different group to those interviewed during the day.…”
Section: Data Collectionmentioning
confidence: 98%